Organizing credibility: discursive and organizational orthodoxy on the borders of ecology and politics - Kinchy, Abby J.; Kleinman, Daniel Lee (2003)
In the present paper, we show that in its efforts to maintain credibility and claim social relevance, the Ecological Society of America (ESA) and its members repeatedly negotiate a boundary between science and politics. While the boundaries of ecology are flexibly defined, contingent on political context and what is at stake, they are also shaped and constrained by the already constructed social world. Several factors shape the ESA's boundary-work: (1) historically resonant discourses of both value-freedom and the utility of science; (2) national politics, including social movements and the demands of funding bodies; (3) the structure and actions of other, often more prestigious, scientific societies; and (4) established orthodoxies of scientific behaviour. We contribute to the scholarly literature on creditibility in science by showing that the construction of boundaries between science and politics is, in some cases, better understood as the reproduction of the already constructed social world than as a product of strategic efforts in pursuit of individual interests. - Reproduced.
Keywords: Ecology